Editorial: Towards a psychophysiological approach in physical activity, exercise, and sports - Forte, Pedro (2023)
This Research Topic aims to look at specific themes related to physiological stress and mental well-being. Additionally, we aim to provide evidence to coaches and sports scientists highlighting the relationship between training and competition demands, related to performance. We also want to analyze the effects of strength and conditioning training, and coaching effects (acute and chronic) on psychological and physiological. Finally, it is our intention to provide scientific literature with evidence for a relationship between movement, behavior and cognition with physiological performance: the psychophysiological approach.